Gauri idol taken in a grand procession for visarjan - Mumbai Archive Project Team (Jio Institute, 2024)
On the third day, the Gauri idol is taken in a grand procession for visarjan (immersion). This ritual symbolizes the return of the Goddess to her divine abode and is accompanied by singing, dancing, and the chanting of mantras (a word or sound that is believed to have a special spiritual power).